An inconstant landscape : the Maya kingdom of El Zotz, Guatemala - Garrison, Thomas G. (Thomas Gardner); Houston, Stephen D. (University Press of Colorado, 2018)
"Six years of archaeological survey around the Maya kingdom of El Zotz a complex picture of a dynamic landscape that experienced numerous fluctuations over the course of 2000 years of occupation-it serves as a test-case of political debility and strength during the height of dynastic struggles"--Provided by publisher